A Protonated Water Cluster as a Transient Proton‐Loading Site in Cytochrome c Oxidase. (19th August 2016) - Supekar, Shreyas; Gamiz‐Hernandez, Ana P.; Kaila, Ville R. I.
Abstract: Cytochrome c oxidase (CcO) is a redox‐driven proton pump that powers aerobic respiratory chains. We show here by multi‐scale molecular simulations that a protonated water cluster near the active site is likely to serve as the transient proton‐loading site (PLS) that stores a proton during the pumping process. The p K a of this water cluster is sensitive to the redox states of the enzyme, showing distinct similarities to other energy converting proton pumps.